The Artistic Value of Mantle of the Expert: Dorothy Heathcote's dramatic-inquiry approach to teaching and learning: a Belgian Research Project - Selderslaghs, Bob (IJRDO- Journal of Educational Research, 2018)
This article gives an insight on the first results of a Belgian Research Project where Bob Selderslaghs examines the artistic value of the Mantle of the Expert approach in a Flemish primary school. He focuses on artistic roles that students can adopt while studying the curriculum.